Cryptococcal Antigen Screening in Asymptomatic HIV-Infected Antiretroviral Naïve Patients in Cameroon and Evaluation of the New Semi-Quantitative Biosynex CryptoPS Test - Temfack, Elvis; Kouanfack, Charles; Mossiang, Leonella; Loyse, Angela; Fonkoua, Marie C.; Molloy, Síle F.; Koulla-Shiro, Sinata; Delaporte, Eric; Dromer, Françoise; Harrison, Thomas; Lortholary, Olivier (Frontiers in Microbiology, 2018)
Background Cryptococcal meningitis (CM) is a major cause of AIDS-related mortality in Africa. Detection of serum cryptococcal antigen (CrAg) predicts development of CM in antiretroviral (ART) naïve HIV-infected patients with severe immune depression. Systematic pre-ART CrAg screening and pre-emptive oral fluconazole is thus recommended. We postulated that a semi-quantitative CrAg screening approach could offer clinically relevant advantages. Methods ART-naïve asymptomatic adult outpatients with <100 CD4 cells/mm3 presenting to the Yaoundé Central Hospital, Cameroon were screened for CrAg using the IMMY lateral flow assay (LFA). CrAg positive patients were consented for lumbar puncture and those with proven CM were treated with combination antifungal therapy and those with no CM were offered long-term oral fluconazole. Simultaneous on-site evaluation of CrAg detection using the new LFA Biosynex CryptoPS® test was performed and both tests were subsequently compared to a reference commercialized CrAg enzyme immunoassay (EIA). Results Prevalence of serum CrAg in 186 screened adults was 7.5% (95%CI: 4.5 – 12.4). In CrAg positive patients, CM prevalence was 45.5% (95%CI: 18.3 – 75.7). IMMY and Biosynex CryptoPS strongly agreed in serum, plasma, and cerebrospinal fluid (Kappa: 98.4%, 99.5%, 100%, respectively, p<0.001),and disagreed in urine (29 isolated positive CrAg in urine with IMMY, none with Biosynex and none of whom had proven CM). Compared to EIA , serum specificities were 96.6% and 98.3%, respectively. With Biosynex CryptoPS, all CM patients were serum T2-band positive compared to none without CM. Median EIA reciprocal titre was 160 (IQR: 13.5 – 718.8) and titres >160 strongly correlated with proven CM and Biosynex CryptoPS T2-band positivity. During the 1-year follow up period, there was no incident case of CM among screened patients and overall incidence of all-cause mortality was 31.5 per 100 person-years-at-risk (95%CI: 23.0 – 43.1). Conclusion HIV-associated asymptomatic cryptococcosis is common in Cameroon, warranting integrated systematic screening and treatment. Biosynex CryptoPS holds promise, at point of care, for rapidly stratifying CrAg positive patients for optimal management including lumbar puncture and combination antifungal therapy when needed.